Local and Nonlocal Land Surface Influence in European Heatwave Initial Condition Ensembles. Issue 23 (13th December 2019) - Merrifield, A. L.; Simpson, I. R.; McKinnon, K. A.; Sippel, S.; Xie, S.‐P.; Deser, C.
Abstract: Dry land surface conditions have been shown to amplify extreme heat events in Europe, but the extent to which this influence involves modification of the overlying atmospheric circulation has yet to be fully established. Here, this issue is addressed using two Community Earth System Model ensembles, with the same heatwave‐inducing atmospheric circulation pattern imposed over different land surface states. These two ensembles differ in the vertical level above which the circulation is constrained (surface vs. upper troposphere). Soil moisture anomalies are found to play an important role in dictating heatwave intensity among ensemble members. The heatwave is approximately 0.1°C hotter per standard deviation soil moisture reduction when the troposphere is free to respond to surface conditions than when it is constrained, implying that a portion of the land surface influence involves feedbacks through the atmospheric circulation. The additional atmospheric response also allows for nonlocal heatwave amplification in subsequent months. Plain Language Summary: Seasonally persistent European heatwaves are socioeconomically costly. Though established by atmospheric circulation patterns, heatwaves can be intensified by dry land surface conditions, increasing societal risks. Here, we show that the manner in which dry land surface conditions affect European heatwave intensity is twofold: through local heating and through changes to the structure of the atmosphere. The additional influence of the land surface on the atmosphere can make the same European heatwave up to 0.4°C hotter overall and can cause surface drying in other regions. This nonlocal mechanism leads to hotter conditions in those regions in subsequent months. Key Points: By constraining atmospheric circulation, a seasonally persistent European heatwave is imposed over different initial land surface states The prescribed heatwave is amplified by local dryness directly and indirectly through the modification of the near‐surface atmosphere The atmospheric response to surface dryness allows for an additional 0.1°C of warming per standard deviation of soil moisture drying